Oxide scale growth and presumed exfoliation in a 700 °c or higher steam condition: A simulation study for future operations of ultra-supercritical power plants - Yeo W.H.; Fry A.T.; Purbolaksono J.; Ramesh S.; Inayat-Hussain J.I.; Liew H.L.; Hamdi M. (Elsevier, 2023)
The world is facing the challenge of providing abundant and affordable electricity to meet the need of a growing global population, while lowering and controlling CO2 emissions. Both of these goals can be met through improving the efficiency of the boiler through increasing the operating pressure and temperature, although increasing steam temperature has been reported to be more economical than raising steam pressure. However, higher temperatures may lead to increased boiler tube failure through steam-side oxidation and fireside corrosion mechanisms. Ni-based alloys are candidate materials for these aggressive conditions. The study reported here is evaluating steam-side oxide growth in a given length of superheater and reheater tubes of ultra-supercritical boilers operating at 700 °C or higher/35 MPa steam condition under different presumed service conditions. A simple and inexpensive procedure to estimate the oxide scale growth and the metal temperature increase in a boiler tube over a period of time is proposed. Verification of the findings with the actual data from the power plants is provided. The oxide scale growth rates of nickel-based alloys at steam temperatures up to 750 °C seemed to be tolerable in service based on the procedures demonstrated here. © 2014 Elsevier B.V.